Lactic acid production from waste sugarcane bagasse derived cellulose - Adsul, Mukund G.; Varma, Anjanikumar; Gokhale, Digambar V. (Green Chemistry, 2007)
Production of L(+) lactic acid from sugarcane bagasse cellulose, one of the abundant biomass materials available in India, was studied. The bagasse was chemically treated to obtain a purified bagasse cellulose sample, which is much more amenable to cellulase enzyme attack than bagasse itself. This sample, at high concentration (10%), was hydrolyzed by cellulase enzyme preparations (10 FPU g(-1) cellulose) derived from mutants generated in our own laboratory. We obtained maximum hydrolysis (72%), yielding glucose and cellobiose as the main end products. Lactic acid was produced from this bagasse cellulose sample by simultaneous saccharification and fermentation (SSF) in a media containing a cellulase enzyme preparation derived from Penicillium janthinellum mutant EU1 and cellobiose utilizing Lactobacillus delbrueckii mutant Uc-3. A maximum lactic acid concentration of 67 g l(-1) was produced from a concentration of 80 g l(-1) of bagasse cellulose, the highest productivity and yield being 0.93 g l(-1) h(-1) and 0.83 g g(-1), respectively. The mutant Uc-3 was found to utilize high concentrations of cellobiose (50 g l(-1)) and convert it into lactic acid in a homo-fermentative way. Considering that bagasse is a waste material available in abundance, we propose to valorize this biomass to produce cellulose and then sugars, which can be fermented to products such as ethanol and lactic acid.

Utilization of molasses sugar for lactic acid production by lactobacillus delbrueckii subsp delbrueckii mutant Uc-3 in batch fermentation - Dumbrepatil, Arti; Adsul, Mukund G.; Chaudhari, Shivani; Khire, Jayant Malhar; Gokhale, Digambar V. (Applied and Environmental Microbiology, 2008)
Efficient lactic acid production from cane sugar molasses by Lactobacillus delbrueckii mutant Uc-3 in batch fermentation process is demonstrated. Lactic acid fermentation using molasses was not significantly affected by yeast extract concentrations. The final lactic acid concentration increased with increases of molasses sugar concentrations up to 190 g/liter. The maximum lactic acid concentration of 166 g/liter was obtained at a molasses sugar concentration of 190 g/liter with a productivity of 4.15 g/liter/h. Such a high concentration of lactic acid with high productivity from molasses has not been reported previously, and hence mutant Uc-3 could be a potential candidate for economical production of lactic acid from molasses at a commercial scale.

Biochemical characterization of two xylanases from yeast Pseudozyma hubeiensis producing only xylooligosaccharides - Adsul, Mukund G.; Bastawade, Kulbhushan B.; Gokhale, Digambar V. (Bioresource Technology, 2009)
Two distinct xylanases from Pseudozyma hubeiensis NCIM 3574 were purified to homogeneity. The molecular masses of two native xylanases were 33.3 kDa (PhX33) and 20.1 kDa (PhX20). PhX33 is predominant with alpha-helix and PhX20 contained predominantly beta-sheets. Xylanase, PhX33, possesses three tryptophan and one carboxyl residues at the active site. The active site of PhX20 comprises one residue each of tryptophan, carboxyl and histidine. Carboxyl residue is mainly involved in catalysis and tryptophane residues are solely involved in substrate binding. Histidine residue present at the active site of PhX20 appeared to have a role in substrate binding. Both the xylanases produced only xylooligosaccharides (XOS) with degree of polymerization (DP) 3-7 without formation of xylose and xylobiose. These XOS could be used in functional foods or as prebiotics. Lc ms-ms ion search of cryptic digestion of these xylanases revealed that there is no significant homology of peptides with known fungal xylanase sequences which indicate that these xylanases appear to be new. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cellulase-free xylanase; Pseudozyma hubeiensis; Xylooligosaccharides

Cellulases from penicillium janthinellum mutants: solid-state production and their stability in ionic liquids - Adsul, Mukund G.; Terwadkar, Asawari P.; Varma, Anjanikumar; Gokhale, Digambar V. (Bioresources, 2009)
The cellulase production by P. janthinellum mutants on lignocellulosic material such as cellulose or steam exploded bagasse (SEB) in combination with wheat bran was studied in solid state fermentation (SSF). One of the mutants, EU2D21, produced the highest levels of endoglucanase (3710 IU g(-1) carbon source) and beta-glucosidase (155 IU g(-1) carbon source). Ionic liquids are so-called green solvents that have become attractive for biocatalysis. Stability of mutant cellulases was tested in 10-50% of the ionic liquid 1-butyl-3-methylimidazolium chloride ([bmim]Cl). FPA and CMCase were significantly stable in 10% ionic liquid after 5h. beta-glucosidase showed 85% of its original activity after 5 h incubation in 30% ionic liquid and retained 55% of its activity after 24 h. This enzyme preparation hydrolyzed ionic-liquid-treated SEB completely in 15 h in the presence of 20% ionic liquid. These studies revealed that there is no need of regenerating cellulose after ionic liquid treatment, since cellulase of mutant strain was found to be significantly stable in the ionic liquid.
Keywords: Cellulase stability; Ionic liquid; Mutant cellulase; Solid state fermentation

D-(-)-Lactic acid production from cellobiose and cellulose by Lactobacillus lactis mutant RM2-24 - Singhvi, Mamta; Joshi, Dipti; Adsul, Mukund G.; Varma, Anjanikumar; Gokhale, Digambar V. (Green Chemistry, 2010)
Lactobacillus lactis mutant RM2-24 utilizes cellobiose efficiently, converting it into D-(-)-lactic acid. Cellobiose-degrading enzyme activities were determined for whole cells, cell extracts and disrupted cells. Aryl-beta-glucosidase activity was detected in whole cells and disrupted cells, suggesting that these activities are confined to the cells. The mutant produced 80 g l(-1) of lactic acid from 100 g l(-1) of cellobiose with 1.66 g l(-1) h(-1) productivity. Production of D-lactic acid from different cellulose samples was also studied. The cellulose samples at high concentration (10%) were hydrolyzed by cellulase enzyme preparation (10 FPU g(-1) cellulose) derived from Penicillium janthinellum mutant EU1 generated in our own laboratory. We obtained a maximum 72% hydrolysis, yielding glucose and cellobiose as the main end products. Lactic acid was produced from these cellulose samples by simultaneous sacchari. cation and fermentation (SSF) in a media containing a cellulase enzyme preparation derived from Penicillium janthinellum mutant EU1 and cellobiose utilizing Lactobacillus lactis mutant RM2-24. A maximum lactic acid concentration of 73 g l(-1) was produced from a concentration of 100 g l(-1) of bagasse-derived cellulose, the highest productivity and yield being 1.52 g l(-1) h(-1) and 0.73 g g(-1), respectively. Considering that bagasse is a waste material available in abundance, we propose to use this biomass to produce cellulose and then sugars, which can be fermented to valuable products such as ethanol and lactic acid.

Lipase of aspergillus niger NCIM 1207: a potential biocatalyst for synthesis of isoamyl acetate - Mhetras, Nutan; Patil, Sonal; Gokhale, Digambar V. (Indian Journal of Microbiology, 2010)
Commercial lipase preparations and mycelium bound lipase from Aspergillus niger NCIM 1207 were used for esterification of acetic acid with isoamyl alcohol to obtain isoamyl acetate. The esterification reaction was carried out at 30 degrees C in n-hexane with shaking at 120 rpm. Initial reaction rates, conversion efficiency and isoamyl acetate concentration obtained using Novozyme 435 were the highest. Mycelium bound lipase of A. niger NCIM 1207 produced maximal isoamyl acetate formation at an alcohol/acid ratio of 1.6. Acetic acid at higher concentrations than required for the critical alcohol/acid ratio lower than 1.3 and higher than 1.6 resulted in decreased yields of isoamyl acetate probably owing to lowering of micro-aqueous environmental pH around the enzyme leading to inhibition of enzyme activity. Mycelium bound A. niger lipase produced 80 g/l of isoamyl acetate within 96 h even though extremely less amount of enzyme activity was used for esterification. The presence of sodium sulphate during esterification reaction at higher substrate concentration resulted in increased conversion efficiency when we used mycelium bound enzyme preparations of A. niger NCIM 1207. This could be due to removal of excess water released during esterification reaction by sodium sulphate. High ester concentration (286.5 g/l) and conversion (73.5%) were obtained within 24 h using Novozyme 435 under these conditions.
Keywords: Aspergillus niger NCIM 1207; Fusel oil; Isoamyl acetate formation; Mycelium bound lipase; Novozyme 435

Protoplast formation and regeneration in lactobacillus delbrueckii - Singhvi, Mamta; Joshi, Dipti; Gaikaiwari, Shalaka A.; Gokhale, Digambar V. (Indian Journal of Microbiology, 2010)
Method for production and regeneration of Lactobacillus delbrueckii protoplasts are described. The protoplasts were obtained by treatment with a mixture of lysozyme and mutanolysin in protoplast buffer at pH 6.5 with different osmotic stabilizers. The protoplasts were regenerated on deMan, Rogosa and Sharpe (MRS) with various osmotic stabilizers. Maximum protoplast formation was obtained in protoplast buffer with sucrose as an osmotic stabilizer using a combination of lysozyme (1 mg/ml) and mutanolysin (10 mu g/ml). Maximum protoplast regeneration was obtained on MRS medium with sucrose (0.5 M) as an osmotic stabilizer. The regeneration medium was also applicable to other species of lactobacilli as well. This is, to our knowledge, the first report on protoplast formation and efficient regeneration in case of L. delbrueckii.
Keywords: Lactobacillus delbrueckii; Protoplast formation; Protoplast regeneration

Combined strategy for the dispersion/dissolution of single walled carbon nanotubes and cellulose in water - Adsul, Mukund G.; Rey, Diego A.; Gokhale, Digambar V. (Journal of Materials Chemistry, 2011)
Co-dispersion of native cellulose and single walled carbon nanotubes in water is demonstrated. The pH of the water should be between 6 and 10 for better dispersion. Raman spectra confirm debundling of nanotubes in water and FTIR spectra reveal that the co-solubility is likely caused through disruption of intramolecular hydrogen bonds in the cellulose by hydroxyl groups present on nanotubes surface and the creation of intermolecular hydrogen bonds between cellulose and carbon nanotubes. This is a very simple method for co-dispersion/dissolution of nanotubes and cellulose in water without covalent modifications and expands the repertoire of nanotube modification strategies that are amenable to biological applications.

Hyper-production of beta-glucosidase and beta-xylosidase by aspergillus niger NCIM 1207 In Xylan-Containing Media - Khisti, Ujwala; Bastawade, Kulbhushan B.; Gokhale, Digambar V. (Bioresources, 2011)
Aspergillus niger NCIM 1207 produced significantly high levels of beta-glucosidase and beta-xylosidase activities in submerged fermentation. Cellulose induced only beta-glucosidase, while xylan induced both beta-glucosidase and beta-xylosidase activities. Both the enzymes of this strain were found to undergo catabolite repression in the presence of high concentrations of glucose and glycerol. The sudden drop in pH of the fermentation medium below 3.5 caused the inactivation of enzymes when the fungus was grown in glycerol-containing media at lower temperatures. The growth of the organism at 36 degrees C led to an increase in pH of the fermentation above 6.0 that affected beta-xylosidase activity significantly. Highest levels of beta-glucosidase ((19 IU mL(-1) or 633 IU g(-1) of substrate) and beta-xylosidase (18.7 IU/mL(-1) or 620 IU g(-1) of substrate) activities were detected when A. niger was grown at 30 degrees C for first five days followed by further incubation at 36 degrees C. Such a process of growing the organism at lower temperatures (growth phase) followed by producing the enzymes at higher temperatures (production phase) in case of fungal systems has not been reported so far. The zymogram staining of the beta-glucosidase demonstrated that A. niger produced only single species of beta-glucosidase. We feel that A. niger NCIM 1207 is a potential candidate to produce both beta-glucosidase and beta-xylosidase in high amounts that can be used to supplement commercial cellulase preparations.
Keywords: Aspergillus niger NCIM 1207; beta-glucosidase production; beta-xylosidase production

Biomass to biodegradable polymer (PLA) - Singhvi, Mamata; Gokhale, Digambar V. (RSC Advances, 2013)
Lignocellulosic biomass is renewable and cheap, and it has the potential to displace fossil fuels for the production of fuels and chemicals. Biomass derived lactic acid is an important compound that can be used as a chemical platform for the production of a variety of important chemicals on a large scale. The quality of the monomers of lactic acid and lactide, as well as the chemical changes induced during polymerization and processing, are crucial parameters for controlling the properties of the resulting polylactic acid (PLA) products. In this review, we outline the process of exploiting biomass for the production of polylactic acid, a biodegradable polymer which is well-known as a sustainable bioplastic material.

Supplementation of medium with diammonium hydrogen phosphate enhanced the D-lactate dehydrogenase levels leading to increased D-lactic acid productivity - Singhvi, Mamata; Jadhav, Akanksha; Gokhale, Digambar V. (Bioresource Technology, 2013)
The production of D-lactic acid by Lactobacillus lactis RM2-24 was investigated using modified media to increase the efficiency of the fermentation process. The results indicated that the addition of 5 g/l peptone and 1 g/l (NH4)(2)HPO4 enhanced D-lactic acid production by 32%, as compared to that obtained from non supplemented media, with a productivity of 3.0 g/l/h. Lactate dehydrogenase (LDH) expression profile in these different media was studied which resulted in appearance of additional LDH isoform produced by cells when they were grown in HSYE supplemented with (NH4)(2)HPO4. The additional LDH appears to be L-LDH contributing to production of L-lactic acid in the fermented broth. This is totally new information in the lactic acid fermentation and could be very useful to industries engaged in D-lactic acid production. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: D(-) lactic acid production; Lactate dehydrogenase; Lactobacillus delbrueckii Uc-3; Lactobacillus lactis RM2-24

Lignocellulose processing: a current challenge - Singhvi, Mamata S.; Chaudhari, Shivani; Gokhale, Digambar V. (RSC Advances, 2014)
Lignocellulosic biomass, of which inedible crops are a renewable source, is expected to become one of the key renewable energy resources in the near future, to deal with global warming and the depletion of conventional fossil fuel resources. It also holds the key to supplying society's basic needs for the sustainable production of chemicals and fuels without impacting the human food supply. Despite this, the production of 2nd generation biofuels and chemicals has not yet been commercialized. Therefore, the challenges involved in the production of lignocellulosic biomass derived fuels and chemicals must be addressed. The search for economic pretreatment methods has been recognized as one of the main hurdles for the processing of biomass to biofuels and chemicals. The conversion of all biomass components, lignin in particular, would greatly contribute to the economic viability of biomass based processes for 2nd generation biofuels and chemicals. The highly organized crystalline structure of cellulose presents an obstacle to its hydrolysis. Hydrolysis of lignocellulose carbohydrates into fermentable sugars requires a number of different biomass degrading enzymes such as cellulases and hemicellulases. Still, a number of technical and scientific issues within pretreatment and hydrolysis remain to be solved. Depending on the raw material and pretreatment technology, the enzyme mixtures must be designed to degrade biomass carbohydrates. Rapid advances in enzyme, microbial and plant engineering would provide the necessary breakthroughs for the successful commercialization of biomass derived fuels and chemicals.

Biocatalyst development for lactic acid production at acidic pH using inter-generic protoplast fusion - Singhvi, Mamata; Gurjar, Gayatri; Gupta, Vidya; Gokhale, Digambar V. (RSC Advances, 2015)
Global warming and environmental problems force us to develop sustainable processes based on the use of biocatalysts that are eco-friendly with the least potential toxicity. Lactic acid fermentation at neutral pH generates a large amount of gypsum during down-stream processing. Hence it is essential to develop Lactobacillus strains which produce lactic acid at acidic pH thus making the whole downstream process environmentally friendly. Fusant F3 was generated using protoplast fusion between Lactobacillus delbrueckii Mut Uc-3 and Acetobacter pasteurianus NCIM 2314 on solid media at pH 4.0. Fusant F3 was further treated by UV irradiation to generate a mutant, FM1, with improvements in acid tolerance which produced five-fold more lactic acid than the parent strain at acidic pH. The molecular studies using RAPD markers demonstrated that the fusant is derived from both the parental strains, Acetobacter and Lactobacillus and the mutant is derived from the fusant. The utilization of such acid tolerant strains could be able to produce free lactic acid at acidic pH without using neutralizing agents and will offer an effective means for designing environmentally benign processes for lactic acid production.

Biomass exploitation - a challenge finding its way to reality - Singhvi, Mamata S.; Gokhale, Digambar V. (Current Science, 2015)
Lignocellulosic biomass holds the key to supplying the basic needs of society for sustainable production of chemicals and fuels without impacting the human food supply. The production of second-generation biofuels and chemicals from lignocellulosic biomass has not yet been commercialized due to its complex and recalcitrance structure. Therefore, the challenges involved in the production of lignocellulosic biomass-derived fuels and chemicals must be addressed. Search for economic pretreatment methods has been recognized as one of the main hurdles for processing of biomass to biofuels and chemicals. The conversion of all biomass components, lignin in particular, would greatly contribute to the economic viability of biomass-based processes for second-generation biofuels and chemicals. Hydrolysis of lignocellulose carbohydrates into fermentable sugars requires a suitable cellulase enzyme cocktail acting on both raw as well as pretreated biomass. Depending on raw material and pretreatment technology, the enzyme mixtures must be designed to degrade biomass carbohydrates. Recent publications on GVL-pretreatment to solubilize and degrade carbohydrates in biomass and CelA enzyme acting on raw biomass would probably meet the challenges in biomass conversion technologies.

Stimulation of d - and l -lactate dehydrogenases transcriptional levels in presence of diammonium hydrogen phosphate resulting to enhanced lactic acid production by Lactobacillus strain - Singhvi, Mamata S.; Zendo, Takeshi; Iida, Hiroshi; Gokhale, Digambar V.; Sonomoto, Kenji (Journal of Bioscience and Bioengineering, 2017)
The present study revealed the effect of nitrogen sources on lactic acid production and stimulation of d- and l-lactate dehydrogenases (LDH) of parent Lactobacillus lactis NCIM 2368 and its mutant RM2-24 generated after UV mutagenesis. Both the parent and mutant strains were evaluated for d-lactic acid production in control and modified media. The modified media did not show remarkable effect on lactic acid production in case of parent whereas mutant exhibited significant enhancement in d-lactic acid production along with the appearance of l-lactic acid in the broth. Both LDH activities and specific activities were found to be higher in mutant than the parent strain. These results suggested that the diammonium hydrogen phosphate in modified media triggered the expression of LDH genes leading to enhanced lactic acid production. This observation has been proved by studying the expression levels of d- and l-LDH genes of parent and mutant in control and modified media using quantitative RT-PCR technique. In case of mutant, the transcriptional levels of d-LDH and l-LDH increased ∼17 fold and ∼1.38 fold respectively in modified medium compared to the values obtained with control medium. In case of parent, no significant change in transcriptional levels of d- and l-LDH was found when the cells were grown in either control medium or modified medium. This study suggested that the mutant, RM2-24 has l-LDH gene which is expressed in presence of (NH4)2HPO4 resulting in l-lactic acid production. Co-production of l-lactic acid in d-lactic acid fermentation may be detrimental in the PLA production.

Lignocellulosic biomass: hurdles and challenges in its valorization - Singhvi, Mamata S.; Gokhale, Digambar V. (Applied Microbiology and Biotechnology, 2019)
Lignocellulosic biomass (LCB) is globally available and sustainable feedstock containing sugar-rich platform that can be converted to biofuels and specialty products through appropriate processing. This review focuses on the efforts required for the development of sustainable and economically viable lignocellulosic biorefinery to produce carbon neutral biofuels along with the specialty chemicals. Sustainable biomass processing is a global challenge that requires the fulfillment of fundamental demands concerning economic efficiency, environmental compatibility, and social responsibility. The key technical challenges in continuous biomass supply and the biological routes for its saccharification with high yields of sugar sources have not been addressed in research programs dealing with biomass processing. Though many R&D endeavors have directed towards biomass valorization over several decades, the integrated production of biofuels and chemicals still needs optimization from both technical and economical perspectives. None of the current pretreatment methods has advantages over others since their outcomes depend on the type of feedstock, downstream process configuration, and many other factors. Consolidated bio-processing (CBP) involves the use of single or consortium of microbes to deconstruct biomass without pretreatment. The use of new genetic engineering tools for natively cellulolytic microbes would make the CBP process low cost and ecologically friendly. Issues arising with chemical characteristics and rigidity of the biomass structure can be a setback for its viability for biofuel conversion. Integration of functional genomics and system biology with synthetic biology and metabolic engineering undoubtedly led to generation of efficient microbial systems, albeit with limited commercial potential. These efficient microbial systems with new metabolic routes can be exploited for production of commodity chemicals from all the three components of biomass. This paper provides an overview of the challenges that are faced by the processes converting LCB to commodity chemicals with special reference to biofuels.
Keywords: Biomass pretreatment; Biomass supply chain; Cellulosic ethanol; Consolidated bio-processing; Lignocellulosic biomass (LCB)